Integrated nutrient management in COD x WCT hybrid coconut under alluvial clay-loam soil of Assam - Nath, J.C.; Arulraj, S.; Maheswarappa, H.P. (Journal of Plantation Crops, 2012)
A field experiment was conducted in alluvial clay-loam soil at the Horticultural Research Station, Kahikuchi of Assam Agricultural University under All India Co-ordinated Research Project on Palms from 2003 to 2007 to study the effect of integrated nutrient management treatments on COD x WCT hybrid coconut taking 27 treatment combinations with three levels each of N (0, 500, 1000 g/palm/year, where 50% N was substituted by vermicompost on N equal nutrient basis), P2O5 (0, 250, 500 g/palm/year) and K2O (0, 1000, 2000 g/palm/year). The results revealed significant influence of the integrated nutrient treatments on number of functional leaves in the crown, number of female flowers, nut setting, nut yield per palm per year and copra content per nut. The highest values for all these characters were obtained under higher level of K application. However, the highest average nut yield of 111nuts/palm/year and benefit cost ratio of 2.02 were recorded in the treatment N1P2K2 (500 g N wherein 50% N substituted by vermicompost, 500 g P2O5 and 2000 g K2O/palm/year), while the lowest nut yield (44 nuts/palm/year) and benefit cost ratio of 0.20 were recorded in the treatment N0P0K0 and N2P2K0, respectively. The integrated nutrient treatments also improved the soil pH, organic carbon content, available N, P and K content of the soil and the leaf NPK contents of the palms under study.